Gross brain morphology of Hypoptopomatinae and Neoplecostominae (Siluriformes: Loricariidae): Comparative anatomy and phylogenetic implications - Rosa, Alaina Cristine [UNESP]; Martins, Fernanda de Oliveira; Langeani, Francisco [UNESP] (Hindawi, 2021)
Hypoptopomatinae and Neoplecostominae include about 250 valid species, a substantial portion of loricariid catfishes. Although the relationships among the members of these subfamilies have been inferred by many authors, the most recent hypotheses based on morphological and molecular data differ widely. Herein, we provide new data on the morphology of the central nervous system, and evaluate the usefulness of these characters in phylogenetic inference. To accomplish this, we characterized the gross brain morphology of those catfishes, and analyzed 54 neuroanatomical characters in a total of 40 terminal taxa representing Hypoptopomatinae and Neoplecostominae, and also members of Delturinae and Hypostominae as outgroups. Hypoptopomatinae and Neoplecostominae are recovered as separate subfamilies, and most of our results are compatible with morphology-based analyses. We conclude that neuroanatomy provides an informative source of new characters with strong phylogenetic signal at all recovered taxonomic levels.
Keywords: catfishes; central nervous system; neuroanatomy; phylogeny; systematics